Pasting characteristics of fresh yams (Dioscorea spp.) as indicators of textural quality in a major food product: pounded yam - Otegbayo, B.; Aina, J.; Asiedu, Robert; Bokanga, M. (Elsevier, 2006)
Low efficiency of available screening procedures constrains breeding and selection of yams (Dioscorea spp.) towards high textural quality of food products made from their tubers. This study was undertaken to determine the potential usefulness of pasting characteristics of fresh yams as rapid indicators of food textural quality in Ô pounded yam Õ, a staple food for millions of yam consumers, especially in West and Central Africa. Significant associations (P< 0.05) were found, through canonical correlation analysis, between pasting characteristics of fresh yams from six varieties, each, of Dioscorea rotundata and Dioscorea alata and the textural quality of pounded yam samples prepared from them. Good textural quality of pounded yam was associated with high peak viscosity, breakdown, final viscosity, holding strength and setback viscosity but with low pasting temperature in the fresh yam.